Rééquilibrage des temps autour de la retraite - Anca Boboc; Jean-Luc Metzger (Temporalités)
The switch to retirement cannot be reduced to a date that separates two disjointed periods of existence in a strict way. On one hand, this switch takes place on a certain duration of time, before and after the formal date when activity stops. One the other hand, retirement is the occasion to undertake activities, whether new ones or the prolongation of former ones, that spring from the individuals’anterior path. More precisely, this particular switch is an occasion to think again on the organisation of social temporalities, and to rearticulate activities in a new way : professional activities (for the ones who keep a job along their retirement) as well as family, artistic, leisure activities. A diversity of retirement paths can be derived from this constatation, as can be observed from the variety of activities that pensioners undertake. This diversity reflects a certain autonomy in the choices that actors make, but it also depends on the choices (« capabilites ») that they can actually reach. In this sense, this paper reviews the advantages and limits of an approach in terms of an « enabling environment », in order to account for the unequal distribution of the capabilities to grasp the opportunities of retirement. More precisely, an « enabling environment » is considered here as all the temporal frameworks for the individuals to build their life paths before retirement. In this sense, three temporal frameworks can be identified : the macro-economic policies, business (or sector) policies, and family biographies. Each of these three frameworks hosts tensions between rigid « accounting time » and more flexible « lived time ». Depending on what will come out of these tensions, individuals will or won’t be able to develop the capabilities to think about their temporal organisation and to invent « time for themselves » when they switch towards retirement.